2020
DOI: 10.1177/1120672120928305
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal aflibercept for management of choroidal neovascularization secondary to angioid streaks

Abstract: Purpose To investigate the effect and the safety of intravitreal aflibercept in patients affected by choroidal neovascularization secondary to angioid streaks with a long-term follow-up. Methods Multicentre, open-label, phase IIb study (EYLEA-STRIE, EudraCT Number 2014-000986-30) involving four Italian centres (IRCCS Ospedale San Raffaele (Milano), Fondazione G.B. Bietti (Roma), Policlinico (Milano), Ospedale Luigi Sacco (Milano)). Patients with active choroidal neovascularization secondary to angioid streaks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…Teixeira et al initially reported the use of intravitreal bevacizumab injection in a patient with subfoveal CNV and AS [ 18 ]. Subsequently, the use of the other anti-VEGF molecules, including ranibizumab and aflibercept, has been reported in the literature [ 7 , 8 , 11 , 12 ]. A retrospective series of 35 eyes with CNV secondary to AS treated with ranibizumab was evaluated by Mimoun et al [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Teixeira et al initially reported the use of intravitreal bevacizumab injection in a patient with subfoveal CNV and AS [ 18 ]. Subsequently, the use of the other anti-VEGF molecules, including ranibizumab and aflibercept, has been reported in the literature [ 7 , 8 , 11 , 12 ]. A retrospective series of 35 eyes with CNV secondary to AS treated with ranibizumab was evaluated by Mimoun et al [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…At a mean follow-up of 24.1 months, the authors noted an improvement or stabilization of BCVA in 30 eyes (85.7%), absence of leakage on fundus fluorescein angiography (FFA) in 23 eyes (65.7%), and reduction or stabilization of central macular thickness (CMT) in 18 eyes (51.5%) [ 19 ]. The Italian EYLEA-STRIE study was a multicentre, open-label, phase IIb study evaluating the safety and efficacy of intravitreal aflibercept therapy on a pro-re-nata basis in 23 eyes of 20 patients with CNV secondary to AS [ 11 ]. At 48 weeks, the authors observed an improvement in BCVA with visual stabilization within 15 letters in 81.8% of the eyes and a significant reduction in CMT [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations